Seaman's Journal : On the Trail with Lewis and Clark - Eubank, Patti Reeder (Nashville, Tenn. : Ideals Childrens Books, 2002)
Seaman, the Newfoundland dog belonging to Meriwether Lewis, keeps an account of their adventures during the journey to the Pacific.
Keywords: Seaman (Dog); Juvenile fiction; Dogs -- Juvenile fiction; Newfoundland dog; Juvenile fiction; Junior fiction